ASPEK GENETIK TALASEMIA - Regar, Joyce (UNIVERSITAS SAM RATULANGI, 2009)
Abstract: Genetic disorders are caused by the presence of affected genes. Thalassaemia, a kind of anaemia due to a genetic disorder, reveals defects in haemoglobin synthesis and chain balance. Signs and symtomps depend on the severity of this disease which vary from slight anemia to facies Cooley, the main characteristic of thalassaemia patients. Diagnosis of thalassaemia is based on clinical signs and symptoms, ethnicity, family history, laboratory examinations, and other supporting examinations. Good management can prolong the life span of thalassaemia patients. Key words: thalassaemia, genetic factor, haemoglobin Abstrak: Penyakit genetik adalah penyakit yang disebabkan oleh karena adanya kelainan dalam susunan gen seseorang. Talasemia merupakan salah satu jenis anemia akibat adanya defek dalam sintesis hemoglobin dan keseimbangan rantainya dengan faktor genetik sebagai penyebab utama. Gejala yang timbul tergantung tingkat keparahan penyakit ini, mulai dari anemia ringan hingga facies Cooley yang merupakan ciri khas pengidap talasemia. Diagnosis talasemia dapat ditegakkan berdasarkan gejala klinik, asal etnis, riwayat keluarga, pemeriksaan keluarga, pemeriksaan laboratorium, dan pemeriksaan penunjang lainnya. Penatalaksanaan yang baik dapat memperpanjang masa hidup dari penderita talasemia. Kata kunci: talasemia, faktor genetik, hemoglobin